Prevalendsi dan Karakteristik Sindroma Mata Kering pada Mahasiswa Semester Enam PSSKPD FK Unud - Widnyana, Nyoman Satria; Juliari, I Gusti Ayu Made; Triningrat, Anak Agung Mas Putrawati (E-Jurnal Medika Udayana; Vol 11 No 8 (2022): E-Jurnal Medika Udayana, 2022)
Dry Eye Syndrome (DES) is a multifactorial disease of the tears and ocular surface that results in symptoms of discomfort, visual disturbance, and tear film instability with potential damage to the ocular surface. This research purposes are to identify the prevalence and the characteristics of DES in medical student, Program Studi Sarjana Kedokteran dan Profesi Dokter (PSSKPD), Fakultas Kedokteran, Universitas Udayana (FK Unud). This research is a descriptive cross-sectional. Ocular Surface Disease Index (OSDI) questionnaire is used to identify the prevalence and risk factors questionnaire such as gender, BMI, history of allergy, frequent use of over the counter (OTC) eye drops, frequent use of contact lens, and sleep quality, is used to identify the characteristics.        This research conducted from March until September 2020. This research use total sampling method managed to collect 199 sample. The results of the study show the prevalence of DES in Preclinical Student of PSSKPD FK Unud is 106 students (52.7%) with 21% on mild severity, 15% on moderate severity, and 18% on severe severity. The characteristics of DES based on gender is 54% for male and 52% for female; on BMI are 40% for <18 kg/m2, 55% for 18-25 kg/m2, 47% for >25 kg/m2; on history of allergy is 47%; on history of OTC drug is 70%; on history of contact lens utilization is 64%; based abnormal quality of sleep is 64%.